KEPUTUSAN TEMPAT PEMBELIAN BERDASARKAN KUALITAS LAYANAN, SUASANA TOKO, DAN PERSEPSI HARGA - Utami Puji Lestari; Ella Anastasya Sinambela (Jurnal Ilmiah Satyagraha, 2022)
Purchase decisions become things that must be observed by customerswhen the process of meeting the needs of products or services. Increasedpurchasing decisions on a product and service are expected by all companies.This is what Hypermart wants for the products they offer. There are severalfactors in purchasing decisions that can affect consumers. These factors includeservice quality, store atmosphere and price perception. This survey was done inthe Hypermart Royal Plaza Surabaya with a sample size of 100 participants, andthe results are in. The author of this research used a non-probability samplingstrategy in conjunction with an incidental sampling approach. Multiple linearregression was used to assess the study data that had been obtained. The findingsof this research revealed that the quality of service, the environment of the shop,and the impression of the pricing had a favorable and substantial impact onpurchase choices at Hypermart Royal Plaza Surabaya. The findings of this studymay be used to further expand this research by including more factors that, inprinciple, have an impact on purchase choices.